Federal innovation platformes’ role in CPE system - Lyudmila V. Averina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The subject of the study is the introduction of innovative infrastructure into the system of additional professional education on the example of the Federal Innovation Site in the field of procurement (hereinafter referred to as the FIP) of the Samara State Economic University from 2013 to 2017. The results of this study are an analysis of the key indicators of FIP on the design of the provision of educational services, the problems of training in procurement. Despite the growing urgency of introducing innovative infrastructure in education, a small amount of research on this topic attracts attention. The results of the research can be used as a basis for the organization of vocational training and retraining, optimization of existing programs of professional development and implementation of innovative projects in these areas.